A national effectiveness trial of an eHealth program to prevent alcohol and cannabis misuse: responding to the replication crisis. Issue 2 (17th January 2022) - Newton, Nicola C.; Chapman, Cath; Slade, Tim; Birrell, Louise; Healy, Annalise; Mather, Marius; McBride, Nyanda; Hides, Leanne; Allsop, Steve; Mewton, Louise; Andrews, Gavin; Teesson, Maree
Abstract: Background: The burden of disease attributable to alcohol and other drug (AOD) use in young people is considerable. Prevention can be effective, yet few programs have demonstrated replicable effects. This study aimed to replicate research behind Climate Schools: Alcohol and Cannabis course among a large cohort of adolescents. Methods: Seventy-one secondary schools across three States participated in a cluster-randomised controlled trial. Year 8 students received either the web-based Climate Schools: Alcohol and Cannabis course (Climate, n = 3236), or health education as usual (Control, n = 3150). Outcomes were measured via self-report and reported here for baseline, 6- and 12-months for alcohol and cannabis knowledge, alcohol, cannabis use and alcohol-related harms. Results: Compared to Controls, students in the Climate group showed greater increases in alcohol- [standardised mean difference (SMD) 0.51, p < 0.001] and cannabis-related knowledge (SMD 0.49, p < 0.001), less increases in the odds of drinking a full standard drink[(odds ratio (OR) 0.62, p = 0.014], and heavy episodic drinking (OR 0.49, p = 0.022). There was no evidence for differences in change over time in the odds of cannabis use (OR 0.57, p = 0.22) or alcohol harms (OR 0.73, p = 0.17). Conclusions: The current study provides support for the effectiveness of the web-based Climate Schools: Alcohol and Cannabis course in increasing knowledge and reducing the uptake of alcohol. It represents one of the first trials of a web-based AOD prevention program to replicate alcohol effects in a large and diverse sample of students. Future research and/or adaptation of the program may be warranted with respect to prevention of cannabis use and alcohol harms.